College Law Enforcement and Security Department Responses to Alcohol‐Related Incidents: A National Study. (17th July 2014) - Bernat, Debra H.; Lenk, Kathleen M.; Nelson, Toben F.; Winters, Ken C.; Toomey, Traci L.
<x xml:space="preserve">Abstract</x> Background Campus police and security personnel are often the first to respond to alcohol‐related incidents on campus. The purpose of this study is to examine how campus law enforcement and security respond to alcohol‐related incidents, and how consequences and communication differ based on characteristics of the incident. Methods Directors of campus police/security from 343 colleges across the United States completed a survey regarding usual practice following serious, underage, and less serious alcohol incidents on and off campus. Results Campus law enforcement and security most commonly reported contacting campus officials. A minority reported issuing citations and referring students to the health center. Enforcement actions were more commonly reported for serious and underage incidents than for less serious incidents. Large (vs. small) colleges, public (vs. private) colleges, and those located in small (vs. large) towns more consistently reported taking actions against drinkers. Conclusions Understanding how campus police and security respond to alcohol‐related incidents is essential for reducing alcohol‐related problems on college campuses.